Technology as a Heritage Partner: Balancing Tradition and Innovation in Bát Tràng Pottery Village - Huong, Le Thi Thu; Viet, Tran Quoc (Journal of Posthumanism, 2025)
This article examines the role of technology in the preservation and development of traditional pottery craft in Bát Tràng Village, Gia Lâm District, Hanoi. Grounded in posthumanist theory, the study approaches technology not as a force opposing tradition, but as a “co-creative partner” within an interactive network of humans, materials, and heritage. Through a case study of Bát Tràng—using field observations and in-depth interviews with workshop owners, artisans, and other stakeholders—the article clarifies how technology, when selectively integrated and respectful of local contexts and indigenous knowledge, can enhance production efficiency, expand creative capacities, and simultaneously maintain the uniqueness and spirit of traditional craft. Bát Tràng represents a dynamic slice of modern Hanoi, where the past, present, and future coexist within hybrid cultural forms that are reshaping urban identity. However, the study also highlights risks, including the erosion of traditional knowledge, product homogenization under market pressures, and over-commercialization. Based on these findings, the article proposes a sustainable technology integration model in which technology does not replace humans but expands the capacity for expression, connection, and heritage transmission. The conclusions contribute to posthumanist theory in the Southeast Asian context and offer practical suggestions for preserving and restructuring traditional craft villages as part of Hanoi’s cultural identity development—an ancient capital now envisioning itself as a regional hub of creative cultural industries.